Broadening the duty in relation to Environmental Impact Assessment across the legal instruments applying in Antarctica - Hemmings, A.; Scott, Karen N.; Rogan-Finnemore, M. (University of Canterbury. Gateway Antarctica., 2007)
An intensifying and ever widening range of human activity occurs in the area south of the Antarctic Convergence. Amongst its various consequences it is reasonable to see increasing environmental pressures. Whilst not all activity occurring here is subject to particular international legal instruments, most is. A cluster of Antarctic-specific instruments, comprising the 1959 Antarctic Treaty, 1972 Convention for the Conservation of Antarctic Seals (CCAS), 1980 Convention on the Conservation of Antarctic Marine Living Resources (CCAMLR) and 1991 Protocol on Environmental Protection to the Antarctic Treaty (Protocol), form what is termed ‘the Antarctic Treaty System’ (ATS) and address a large part of present activity. Whaling and harvesting of Southern blue-fin tuna are regulated under the 1946 International Convention for the Regulation of Whaling (ICRW) through its International Whaling Commission (IWC), and the 1993 Convention for the Conservation of Southern Blue-fin Tuna (CCSBT) through its Commission respectively, legal instruments that are external to the Antarctic Treaty System. Other high seas activities in the region are subject to the 1982 United Nations Convention on the Law of the Sea (UNCLOS). Modern integrated environmental management approaches are largely confined to only two of these six instruments - CCAMLR and the Protocol. The obligation for prior Environmental Impact Assessment (EIA), one of the major tools deployed in modern environmental management globally, is confined to the latter. EIA obligations in the Protocol are coupled with the advance notice obligations of Article VII.5.a of the Antarctic Treaty. Although EIA has been applied to national Antarctic programmes and tourism activities, as a matter of state practice this has (drawing on a number of considerations) generally excluded EIA application to any whaling or fishing activities (although there are exceptions in relation to one state). States active in the region, whatever their positions on whaling and the modalities of other ...